LITERATURE REVIEW: THE ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT ON WORK ENGAGEMENT - Shella Evitananda; Nayla Arifatun Nabila; Mudrika Munawaroh; Unika Prihatsanti; Prasetyo Budi Widodo (Faculty of Psychology, Diponegoro University, 2025)
The purpose of this study was to determine the relationship between perceived organizational support and work engagement among employees. Using the Systematic literature review method with PRISMA guidelines. The search for literature review data used the Scopus, Springer, ProQuest, and Cambridge databases from 2019 to 2023. Through screening and selection results, 6 articles were obtained that met the research inclusion criteria. The findings from this study are that perceived organizational support (POS) has a positive relationship with work engagement. Employees who feel perceived organizational support will increase work engagement and employee creativity more than employees with low levels of perceived organizational support.